Electrochemical Noise Analysis for Different Green Corrosion Inhibitors for Copper Exposed to Chloride Media - Nagiub,A. M. (2017)
Four different herbal compounds, Anise (Pimpinella Anisum), Caraway (CARUM Carvi), Cumin (Cuminum Cyminum) and Hibiscus (Hibiscus Sabdarriffa) have been tested as green corrosion inhibitors for copper exposed to 0.5 M NaCl. The corrosion inhibition has been studied using electrochemical noise analysis (EN) and electrochemical impedance spectroscopy (EIS). The comparative analysis of the results obtained showed that EN is an effective tool for screening of new corrosion inhibitors. Analysis of noise data demonstrated the need of removal of the trends in the potential and current fluctuations during the measurement periods. The results gathered showed very good inhibition efficiency. Generally, EN showed a good correlation with EIS in this study.